Comparison of thermal and mechanical quantitative sensory testing in client-owned dogs with chronic naturally occurring pain and normal dogs. (April 2016) - Freire, Mila; Knazovicky, David; Case, Beth; Thomson, Andrea; Lascelles, B. Duncan X.
Highlights: Chronic pain in dogs can be difficult to effectively control due to the development of central sensitization. Somatosensory processing using mechanical and thermal quantitative sensory testing was evaluated. No differences were found between normal dogs and dogs with degenerative joint disease. Results of QST testing in dogs with chronic pain may be influenced by stress. Abstract: Detecting dogs with central sensitization (CS) secondary to chronic pain is hampered by the current inability to measure this condition. The current study aimed to use quantitative sensory testing (QST) to measure (CS) in normal dogs and dogs with painful degenerative joint disease (DJD). It was hypothesized that QST would differ between these two groups of animals. Mechanical and thermal sensory thresholds obtained in animals with DJD-associated pain on two time points 28 days apart were compared with those of normal dogs. Values of sensory thresholds in DJD dogs obtained 28 days after the first evaluation were significantly lower than the results on the first day of evaluation but no differences were found when these results were compared with those of normal dogs. In conclusion, whether QST is different between dogs with chronic pain and normal dogs needs further investigation using a larger group of animals and age, weight and sex matched groups.